2011
DOI: 10.1103/physreva.84.053613
|View full text |Cite
|
Sign up to set email alerts
|

Atom-atom correlations in time-of-flight imaging of ultracold bosons in optical lattices

Abstract: We study the spatial correlations of strongly interacting bosons in a ground state, confined in a two-dimensional square and a three-dimensional cubic lattice. Using the combined Bogoliubov method and the quantum rotor approach, we map the Hamiltonian of strongly interacting bosons onto U(1) phase action in order to calculate the atom-atom correlations' decay along the principal axis and a diagonal of the lattice-plane direction as a function of distance. Lower tunneling rates lead to quicker decays of the cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…In Refs. [80,362] it was also shown that the correlations along the lattice diagonals are weaker than those parallel to the lattice axes in agreement with Eqs. (261)- (263) and numerical data in Fig.…”
Section: One-body Density Matrixsupporting
confidence: 78%
See 1 more Smart Citation
“…In Refs. [80,362] it was also shown that the correlations along the lattice diagonals are weaker than those parallel to the lattice axes in agreement with Eqs. (261)- (263) and numerical data in Fig.…”
Section: One-body Density Matrixsupporting
confidence: 78%
“…In higher dimensions, no exact results have been reported in the literature for the MI at T = 0. Nevertheless, high-order SCE [80] as well as the quantum rotor approach supplemented by the Bogoliubov theory [362] reveal exponential decay of F a for small J/U in two and three dimensions. In Refs.…”
Section: One-body Density Matrixmentioning
confidence: 99%
“…Instead, some studies have developed novel analytic methods [34][35][36][37]. On the other hand, for BECs in shallow optical lattices, theoretical analysis of phase decoherence in 1D has been extensively performed via an extended Gross-Pitaevskii equation (GPE) approach [38], or via the Truncated Wigner Approximation (TWA) approach [31].…”
Section: Introductionmentioning
confidence: 99%
“…The exact derivation of the quantum rotor approach can be found in [8][9][10][11]. Here we present the general idea behind the method and the final outcome.…”
Section: Modelmentioning
confidence: 99%